Unpeeling Pompeii - Fulford, Michael
Pompeii, recovered from under Vesuvius ash, offers a famous 'frozen moment' in archaeological time: a city as it stood at a certain day. Beyond and beneath the dating evidence visible in its standing buildings is to be found a more archaeological chronology.